2008
DOI: 10.1007/s11468-008-9069-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Scattering Field Interactions and Surface Plasmon Resonance in Coupled Silver Nanospheres

Abstract: Scattering field interactions and surface plasmon resonance (SPR) in coupled silver nanospheres are simulated by using the finite-element method, which includes the influences of near-field enhancements of electric field by the particle sizes, separation distances, propagation directions, as well as the polarizations of the incident wave. The proposed structures exhibit a red-and blue-shifted that can be tuned by varying the particle sizes and the separation distances, respectively. Implications for surface-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 31 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…It denotes that touching silver spheres could get “hot spots” only when the wave polarization direction is parallel to the intersphere axis compared with other polarization directions. The numerical simulations are agree well with EI-Sayed groups in experiments, DDA (Discrete-dipole Approximation) and FEM (Finite Element Method) simulations [42, 47, 48]. The optical properties were previously found in experiment by Nakano [49].…”
Section: Numerical Simulation: Results and Analysissupporting
confidence: 85%
“…It denotes that touching silver spheres could get “hot spots” only when the wave polarization direction is parallel to the intersphere axis compared with other polarization directions. The numerical simulations are agree well with EI-Sayed groups in experiments, DDA (Discrete-dipole Approximation) and FEM (Finite Element Method) simulations [42, 47, 48]. The optical properties were previously found in experiment by Nakano [49].…”
Section: Numerical Simulation: Results and Analysissupporting
confidence: 85%
“…For the thinner t of 9 nm, the hybrid SPR and CPR modes show larger spectral tunabilitiy than that of the thicker one, t = 10 nm. This can be explained in the same way as it is for core-shell nanospheres 43 . For the bonding mode (mode 4), the bonding-like mode (mode 3) and the anti-bonding mode (modes 1–2) with respect to the corresponding transmittance dip, remarkable red-shifts are observed when t is reduced and ε in PNSs is increased (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The LSP occurring at the largest excitation wavelength is known as the dipole LSP [42,43], while resonances at shorter wavelengths are higher-order LSPs. It has been shown that the dipole resonance redshifts or blueshifts for decreasing distance between the metal nanoparticles for parallel or perpendicular polarization (with respect to the dimer axis) of the incoming field, respectively [44]. For parallel polarization, it has been suggested that the relative shift of the resonance wavelength for the dimer depends exponentially on the gap distance between the particles.…”
Section: Example Calculations: Plasmonic Dimermentioning
confidence: 99%